Beeng Köödh Mi Teeni Paar Wun Ócag Ka Jaag Yi Wun Kidï Wänyi Cingi Tyëngpur (Men-A Álor). Jyägø, Twööji Gwøg Kej Ákyel, Kí Siyääsà, Kí Lwøøb Nying-A Nyi Myer: Wänyithinh 3 Kì Ri 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon; Porcuna Ferrer, Anna (2023)
This farmer’s handbook is a companion (https://hdl.handle.net/10568/81286). The three booklets making up this farmer’s handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 1 is available at: [ https://hdl.handle.net/10568/151619 ] and booklet 3 is available at [ https://hdl.handle.net/10568/151622 ].